On the formation of the Kepler-10 planetary system - Terquem, C (2014)
In this paper, we investigate the conditions required for the 3 and 17 Earth mass solid planets in the Kepler-10 system to have formed through collisions and mergers within an initial population of embryos. By performing a large number of N-body simulations, we show that the total mass of the initial population had to be significantly larger than the masses of the two planets, and that the two planets must have built-up farther away than their present location, at a distance of at least a few au from the central star. The planets had to grow fast enough so that they would detach themselves from the population of remaining, less massive, cores and migrate in to their present location. By the time the other cores migrated in, the disc's inner edge would have moved out so that these cores cannot be detected today. We also compute the critical core mass beyond which a massive gaseous envelope would be accreted and show that it is larger than 17 Earth masses if the planetesimal accretion rate onto the core is larger than 10^{-6} Earth mass per year. For a planetesimal accretion rate between 10^{-6} and 10^{-5} Earth mass per year, the 17 Earth mass core would not be expected to have accreted more than about 1 Earth mass of gas. The results presented in this paper suggest that a planetary system like Kepler-10 may not be unusual, although it has probably formed in a rather massive disc.